Large Enterprises as a Factor Triggering Social and Economic Changes in the Polish Countryside outside Metropolitan Areas - Dej, Magdalena (Journal for Geography, 2009)
This article focuses on the analysis of the distribution, characteristics and effects of large businesses in Poland located in rural areas outside the reach of the largest urban centres. The first part of this paper presents the distribution and characteristics of companies in which the level of employment reaches a minimum of 200 people located in non-metropolitan rural areas in Poland. The second part contains an analysis of the level of socio-economic development of rural communes, in which enterprises included in the study are located, against the background of all non-metropolitan communes. The last part presents selected aspects of the impact of large economic operators on the local environment using the example of a company with its headquarters in a rural, agricultural area.